Electronic business data processing peripheral equipment occupations, suggested curricula - Office Of Education (DHEW), Washington, DC.; Office of Education (DHEW), Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1964)
Vocational curriculums are suggested for eight electronic business data processing occupations as a guide to training unemployed and underemployed persons. The course outlines and other material were prepared by staff members of the information and training services division of Mcgraw-hill, inc. Consultants included data processing training specialists from industry, administrators in city and state business education departments, and faculty memebers in high schools, colleges, and vocational training institutions. Curriculums are suggested for the occupations--(1) tape librarian, (2) key-punch operator, (3) clerical supervisor, (4) coding clerk, (5) machine-records unit supervisor, (6) statistical clerk, (7) tabulating machine operator, and (8) console operator. Subjects for each occupational course of study are drawn from general office education units, subjects common to two or more occupations, and specialized occupation units, both listed. Program lengths vary from 13 to twenty-two 30-hour weeks. Hours required, unit description, topic outlines for each unit, texts, and other teaching aids are shown for each course of study. Job descriptions and prerequisites for training and employment are given for each occupation. Trainees enrolled in the programs are expected to have completed approximately 10 years of formal education and to have a working knowledge of English and elementary arithmetic. Instructors should be qualified in business data processing. Suggested standards of achievement and an extensive bibliography of texts and references, periodicals, directories, films and filmstrips, and other instructional aids are included. This document is available for 70 cents from superintendent of documents, U.S. Government printing office, Washington, D.C. 20402. (ps)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bibliographies; Curriculum; Curriculum Guides; Data Processing Occupations; Instructional Materials; Labor Force Development; Office Occupations Education; Units of Study; Manpower Development and Training Act